2021
DOI: 10.3389/fcell.2021.779367
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Clinical and Tumor Immune Microenvironment Signature of 5-methylcytosine-Related Regulators in non-small Cell Lung Cancer

Abstract: Background: DNA methylation is an important epigenetic modification, among which 5-methylcytosine methylation (5mC) is generally associated with tumorigenesis. Nonetheless, the potential roles of 5mC regulators in the tumor microenvironment (TME) remain unclear.Methods: The 5mC modification patterns of 1,374 lung adenocarcinoma samples were analyzed systematically. The correlation between the 5mC modification and tumor microenvironment cell infiltration was further assessed. The 5mCscore was developed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The research team found that both the therapeutic benefit and immune cell infiltration were increased in patients with a low 5mC score. 186 Similar studies also found that the group with a high 5mC score was associated with limited cancer immunotherapy sensitivity, and a low 5mC score was associated with a better response to immunotherapy in patients with bladder cancer (BLCA) and lung squamous cell carcinoma (LUSC). 187 These results suggest that the 5mC score may serve as a biomarker for predicting the prognosis of cancer patients and gauging the efficacy of cancer treatments.…”
Section: Introductionmentioning
confidence: 75%
“…The research team found that both the therapeutic benefit and immune cell infiltration were increased in patients with a low 5mC score. 186 Similar studies also found that the group with a high 5mC score was associated with limited cancer immunotherapy sensitivity, and a low 5mC score was associated with a better response to immunotherapy in patients with bladder cancer (BLCA) and lung squamous cell carcinoma (LUSC). 187 These results suggest that the 5mC score may serve as a biomarker for predicting the prognosis of cancer patients and gauging the efficacy of cancer treatments.…”
Section: Introductionmentioning
confidence: 75%
“…For example, in CD4 + T cells from patients with SLE, the levels of the m 5 C writer NSUN2 and methylated m 5 C genes were found to be decreased ( 13 ). In cutaneous melanoma, lung adenocarcinoma, lung squamous cell carcinoma, and other cancer types, bioinformatic analysis have shown that m 5 C regulators modulate the tumor immune microenvironment, act as immunotherapy indicators and were related to patients’ prognosis ( 14 19 , 22 , 60 64 ). These studies firmly proved that m 5 C regulators were differentially expressed and modulated the immunotherapy response in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive study by Liu et al., modifications in the 5mC signature were observed to mediate TME remodeling in lung cancer tissues. Furthermore, the study found that patients with low methylation levels had higher levels of TIL and enhanced clinical response ( 84 ). In another study, the methylation of the promoter region of the Egfl7 gene within the tumor stroma inhibited the expression of CCL2.…”
Section: Induction Of Tls: Current and Potential Strategiesmentioning
confidence: 99%